Seroprevalence of HBsAg positive among women attending a Sexually Transmitted Disease clinic - Miranda, Angélica E. B.; Nogueira, Estephânia G.; Ribeiro, Evanira S.; Area, Kelly R.; Alves, Marta C. (Brazilian Journal of Sexually Transmitted Diseases, 1999)
Objectives: To estimate the seroprevalence of HbsAg positive among women attending a STD cli-nic in Vitoria. Methods: Cross-sectional study was conducted from January to December 1997. All women were invited to take part into the study, they were syste-matically interviewed exploring demographic and patterns of risk behavior. A blood sample was col-lected for testing hepatitis B by HBV surface anti-gen (HBsAg). Detection of HBsAg was achieved in two steps (screening followed by confirmatory test) using an enzyme-linked immunosorbent assay. Res u lts: Fou r-hundred-tem women were tested for hepatitis B. The prevalence rate was 5.4%. Mean age was 28.3 (SD9.3). Regarding education, 7 .1 % were illiterate, 69.2% had only primary education, 20.2% secondary schooland 3.5% college. 46.5% of women were married and 53.5% were not married. Sixty-nine women re- ported one partner in last five years. Previous STDs were reported by 18. 2% women and 6 7% never used condoms. Only 1.4% reported IVDU and 2.5% had history of blood transfusion. Risk factors of their partners included: IVDU 12%, bisexual 2.7%, mul- tiple partners 18%. There was not statistical asso- ciation with the tested variables. lt was observed a higher risk for HIV infection [2.2 (0.59-7.89)] and syphilis [2.6 (0.70-9.65)]. Conclusions : The high prevalence of HBsAg po- sitive found in this study shows the urgent need for vaccination programmes and counseling to this population because they are young and it have the possibility of prenatal transmission.